Community Actions in Preventing Dengue Hemorrhagic Fever (DHF) - Mirensa Elretma Baok; Lidia Br Tarigan; Wanti Wanti; Siprianus Singga; Rr.Sri Endang Pujiastuti; Jiniati Jiniati (Journal of Tropical Diseases and Health Science, 2024)
Dengue Fever is an acute epidemic disease caused by a virus transmitted by Aedes aegypti and Aedesalbopictus. Infected sufferers will have symptoms ranging from mild to high fever, accompanied by headaches, pain in the eyes, muscles and joints, to spontaneous bleeding. There are four different dengue viruses, which can cause dengue fever. Dengue virus is a virus from the genus Flaviviridea, family flaviviridea. This study aims to determine community actions in preventing dengue hemorrhagic fever (DHF) in Liliba sub-district, Kupang City. This type of research is descriptive research with research variables namely the use of abate, how to store clean water, mosquito breeding places (breeding places), the use of repellents/anti-mosquito drugs and the number of free larvae (ABJ). The community's water storage practices were categorized as insufficient at 40.2%, and community actions in water storage were categorized as insufficient at 1.0%. Community actions in mosquito breeding places in Liliba Village were categorized as insufficient at 5.2%. Community actions in the use of mosquito repellents were categorized as insufficient at 19.6%. The larvae-free rate (ABJ) in Liliba Village was 74.2%. It is hoped that stricter evaluation and control of Aedes sp. larvae through PSN-DBD activities will be carried out. More frequent outreach and encouraging the community to implement the 3M activities, leaflets and larvicide distribution will be carried out to break the life cycle of Aedes sp. mosquitoes, which aims to break the chain of dengue transmission and thus increase the Larvae-Free Rate (ABJ)